Humanized scFv Molecule Specific to an Extracellular Epitope of P2X4R as Therapy for Chronic Pain Management - Adinarayana Kunamneni; Karin N. Westlund (Cells, 2025)
Chronic pain affects a significant portion of the population, with fewer than 30% achieving adequate relief from existing treatments. This study describes the humanization methodology and characterization of an effective non-opioid single-chain fragment variable (scFv) biologic that reverses pain-related behaviors, in this case by targeting P2X4. After nerve injury, ATP release activates/upregulates P2X4 receptors (P2X4R) sequestered in late endosomes, triggering a cascade of chronic pain-related events. Nine humanized scFv (hscFv) variants targeting a specific extracellular 13-amino-acid peptide fragment of human P2X4R were generated via CDR grafting. ELISA analysis revealed nanomolar binding affinities, with most humanized molecules exhibiting comparable or superior affinity compared to the original murine antibody. Octet measurements confirmed that the lead, HC3-LC3, exhibited nanomolar binding kinetics (KD = 2.5 × 10−9 M). In vivo functional validation with P2X4R hscFv reversed nerve injury-induced chronic pain-related behaviors with a single dose (0.4 mg/kg, intraperitoneal) within two weeks. The return to naïve baseline remained durably reduced > 100 days. In independent confirmation, the spared nerve injury (SNI) model was similarly reduced. This constitutes an original method whereby durable reversals of chronic nerve injury pain, anxiety and depression measures are accomplished.